Viabilitas Fibroblast Freeze – Dried Amniotic And Fresh Amniotic In BHK21 Cell - Dwi wahyu indrawati; Chiquita Prahasanti; Ernie Maduratna Setyawatie (Eduvest - Journal of Universal Studies, 2024)
Amniotic membrane is the inner most lining of the human placenta that is normally discanded after parturition. The membrane has numerous growth factors, proteins and stem cell reserves that help in accelerating wound healing with regeneration of the lost tissues. The preserved human amniotic membrane is a novel tissue engineerrined biomaterial that is recently trial in field of medicine dentistry to regenerate the lost tissues and accelerate repair. This review paper unfolds the inherent structure, properties, mechanisms and the application of this neglected tissue that makes it a potential for regeneration especially in the field of oral and periodontal surgeries. This research has been conducted to measure the difference of viabilitas fibroblast concentration between fresh amniotic and freeze – died amniotic membranes. Experimental three group test design was exployed with amniotic membrane. Amniotic membrane was divided into two parts. The first parts was without preservation amniotic, the test with BHK21 cell for control group, the second part was with reservation freeze –dried amniotic and the last experiment was with preservation fresh amniotic membrane. The result experiment are viabilitas fibroblast freeze – dried amniotic more than fresh amniotic membrane.